Self efficacy ibu dalam upaya pencegahan ISPA pada balita di Danurejo Mertoyudan - Mufikha, Bintang Fauzia; Mareta, Reni; Kamal, Sodiq (Universitas Muhammadiyah Magelang, 2021)
Abstract Introduction: Children under five are included in the vulnerable group, because when children are under five years old, the immunity of children are not yet fully mature, therefore children are susceptible to disease and infection, one of them is Upper Respiratory Tract Infection, therefore support group is needed in this case is parents especially mothers as the closest to the child to protect and avoid or Prevent the Upper Respiratory Tract Infection. Objective: This study describe mothers self-efficacy and prevention efforts for Upper Respiratory Tract Infection in Danurejo, Mertoyudan and knew the relationship between mothers self-efficacy and prevention of Upper Respiratory Tract Infection. Method: This research was a descriptive correlative study with a total sample of 216 respondents with sampling using Accidental Sampling technique. The Characteristics of respondents in this study were the average age of respondents 30-35 years with a mean of 31.25 years with the majority of high school education level. Some respondents were multiparous mothers (children over 1) with an income level of less than 1 million, with respondents coming from middle to lower economic circles. The profession of most respondents were housewives. Results: The results of this study, form the most respondents showed that mothers self efficacy in Danurejo, Mertoyudan was in the high category with a percentage of 71.8% and a low of 28.2%. In an effort of Prevent the Upper Respiratory Tract Infection in Danurejo, Mertoyudan show that none of the respondents had a low prevention effort for Upper Respiratory Infection, because as many as 165 or 74.4% belonged to the moderate category and 51 or 23.6% belonged to the high category. The results of the correlation test using the Spearman Rank obtained p value 0.000 <0.05 with a positive correlation value of 0.588 which indicated that the correlation between Self Efficacy and efforts to prevent Upper Respiratory Infection is significant with a positive correlation direction with moderate correlation strength.